PENGARUH SIKAP BELAJAR TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI DI KELAS XI IPS SMA NEGERI 8 KOTA JAMBI - Lili Andriani, Novita Sari (Universitas Batanghari Jambi, 2019)
Abstract This study aims to determine description and influence of student learning attitudes in Economics subjects in class XI IPS SMA Negeri 8 Jambi City. Research conducted by researchers is a survey method. The population of 4 (four) classes is 160 students. The sampling technique in this study was proportional random sampling so that 114 students of class XI IPS of SMA Negeri 8 Jambi City were selected. Based on the results of research that researchers have obtained, the learning attitude which consists of: (1) Teacher Approval (TA): which relates to the material presented practice, assignments and requirements set at school shows that the average student on the indicator is 3.26% with a TCR value of 65% this means that the indicators of student learning attitudes on the Teacher Approval (TA) are still quite good. (2) Education Acceptance (AE): students' views of teachers, their behavior in class and ways of teaching with an average of 3.17% with a TCR value of 63%. This means that the indicators of student learning attitudes on Education Acceplance (AE) are still quite good. So it can be concluded that there is an influence of learning attitudes on student learning outcomes in Economics in Class XI IPS SMA Negeri 8 jambi city. This is determined by the Sig 0,000 <0.05. Keywords : Learning Attitudes, Student Learning Outcomes